Ameliorative effects of lycopene on oxidized fish oil-induced growth reduction and hepatic oxidative alterations of Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Guoyong Huang; Weibin Huang; Guangcai Fu; Hengyang Song; Wenshan Cai; Yubin Liu; Yuxuan Han; Yilin Yao; Beiping Tan; Xiaohui Dong (Aquaculture Reports)
This study investigated the effects of adding lycopene to oxidized fish oil diets on the growth and liver health in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂). Fish were fed one of five diets for 8-weeks: (1) FFO: 9 % fresh fish oil (control); (2) OFO: 6 % fresh fish oil and 3 % oxidized fish oil (negative control); (3) LYC1-LYC3: OFO diet supplemented with lycopene (200, 400, 600 mg/kg, respectively). The results showed that the growth performance and whole body crude lipid content were significantly higher in the FFO and LYC groups compared to the OFO group (P < 0.05). Whole body crude lipid was highest in the LYC2 group. In serum biochemical indicators, high-density lipoprotein cholesterol (HDL-C) levels were significantly higher and low-density lipoprotein cholesterol (LDL-C) levels significantly lower in the FFO and LYC2 groups versus the OFO group (P < 0.05). In hepatic antioxidant enzymes, the activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were significantly elevated in the FFO and LYC groups compared to the OFO group (P < 0.05). CAT activity was highest in the LYC2 group. In hepatic antioxidant-related and immune-related gene, LYC groups significantly upregulated the sod, cat, gpx genes and down-regulated the pro-inflammatory factors interleukin-1β (il-1β), interleukin-8 (il-8), and tumor necrosis factor-α (tnf-α) compared to the OFO group (P < 0.05). Conclusion: Dietary lycopene effectively attenuated oxidized fish oil-induced oxidative stress and inflammation in grouper by modulating hepatic antioxidant and immune-related gene expression. Under the experimental conditions, 400 mg/kg lycopene (LYC2 group) demonstrated the optimal protective efficacy.